Analysis of the Effect of Intensive Care Based on Lean Nursing Intervention. (29th September 2021) - Yang, Jing; Xu, Mingjun; Wang, Yili; Gao, Zhiqiang
Abstract : In order to improve the effect of intensive care, this paper proposes a lean nursing intervention method and evaluates the lean nursing intervention through a controlled experiment. According to the actual situation of intensive care, this paper starts with the research from several aspects of patients' ICU nursing time, patients' satisfaction, patients' pathological knowledge familiarity, patients' autonomous nursing, and enthusiasm of patients and their families. Moreover, this paper collects and displays experimental results through mathematical statistics, gives patients lean management concepts and methods based on routine care, and finds that it has good management effects. Thus, lean management concepts and methods can effectively improve the anxiety state of critically ill patients, improve the patient's knowledge of disease, and reduce adverse nursing events to improve patient nursing satisfaction, which is worthy of further promotion in the clinic.